2020
DOI: 10.3389/fpsyg.2020.01418
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation and Evaluation of the South African Adaptation of the JOBS Program

Abstract: No validated intervention that specifically addresses the psychosocial needs of unemployed people exists in the South African context. This study intends to evaluate an evidence-based job-search program, called the JOBS intervention, that is aimed at the self-efficacy, amotivation, and self-esteem related to participants searching for jobs. A quasi-experimental research design was used. Convenient samples were taken of unemployed individuals from two low-income communities (N = 130; experimental group = 69; co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Our results showed that iJobs is a feasible intervention and that the participants found it acceptable. The dropout rate was 36 %, close to the mean percentage (i.e., 35 %) reported in the literature on internet interventions ( Melville et al, 2010 ), but higher as compared to the face-to-face delivery of JOBS (e.g., 14 % in the trial of Paver et al, 2020 ). Moreover, the number and quality of completed modules were high among protocol-compliant participants.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Our results showed that iJobs is a feasible intervention and that the participants found it acceptable. The dropout rate was 36 %, close to the mean percentage (i.e., 35 %) reported in the literature on internet interventions ( Melville et al, 2010 ), but higher as compared to the face-to-face delivery of JOBS (e.g., 14 % in the trial of Paver et al, 2020 ). Moreover, the number and quality of completed modules were high among protocol-compliant participants.…”
Section: Discussionsupporting
confidence: 69%
“…Over the years, the program has been adopted in different countries around the world: Finland ( Vuori and Vinokur, 2005 ), China ( Price et al, 2006 ), Ireland ( Barry et al, 2006 ), Netherlands, Sweden, and South Korea ( Price and Vinokur, 2014 ). Recently was used in South Africa ( Paver et al, 2020 ), and a randomized controlled trial is ongoing in Germany ( Hollederer et al, 2021 ). However, thus far, the program has been delivered solely in a face-to-face setting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The JOBS II intervention [ 4 ] is one of them. JOBS is a job-search intervention intended to promote re-employment and mental health that differentiates itself from others by being studied in and adopted by many countries over the years, such as Finland [ 5 ], China [ 6 ], Ireland [ 7 ], Netherlands, Sweden, and South Korea [ 8 ], South Africa [ 9 ], or Germany [ 10 ].…”
Section: Introductionmentioning
confidence: 99%